The win-stay, lose-switch renesting strategy of a territorial bird endemic to subtropical salt marshes - Sandretti-Silva, Giovanna; Corrêa, Leandro; Amirati, Mariana; Laurino, Ivan Rodrigo Abrão; Passos, Fernando Camargo; Pie, Marcio R.; Bornschein, Marcos R. (Frontiers in Ecology and Evolution, 2024)
IntroductionThe “win-stay, lose-switch” (WSLS) strategy used by birds involves decisions to maintain or alter the characteristics of the subsequent nest according to the outcome of the previous one. In salt marshes, nest failure occurs due to flooding, predation, or tipping, creating a trade-off for nest placement: it should be low enough to avoid predators from above and tipping by the wind, and high enough to avoid flooding. In salt marshes of Southern Brazil, predation from above is carried out by rails that also prey on nests from below, promoting nondirectional pressure capable of neutralizing bird responses. We aim to test the WSLS strategy and to assess its adaptive significance for Formicivora acutirostris, the only thamnophilid endemic to salt marshes. Our general premise is that the adoption of the WSLS strategy would vary in response to the fate of the previous nest, considering also the environment type.MethodsWe evaluated the fate, environment type, height, altitude, and thickness of nests of F. acutirostris in southern Brazil, between 2006 and 2023. We assessed the effects of the nest attributes, tested the adoption of the WSLS strategy, and explored its adaptive significance using generalized linear mixed models. We also examined the influence of factors such as nest environment, nesting timing, and pair age on nest fate and parental behavior.ResultsWe studied 98 renesting cases. Flooded nests were at a lower height than predated, tipped, and successful nests, and tipped nests were thicker than flooded and successful nests. Nest heights differed among environment types. The species adopted the WSLS strategy by increasing nest height after flooding, but we do not support its adaptive significance. No additional factors influenced the behavior of the species.DiscussionAlthough the adoption of the WSLS strategy by F. acutirostris was confirmed regarding the increase in nest height after flooding, it did not result in a significant increase in reproductive success, suggesting that other pressures, such as predation and tipping, are limiting the adaptive potential of this strategy. We emphasize the threat of the high reproductive failure for the conservation of F. acutirostris and proposes reducing predation pressure as an important conservation strategy.